Relationship of Stressors and Psychosocial Support with Occurrence of Post-Traumatic Stress Disorder in Patients with Covid-19 - Ellyamurti, Devanti Octavia; Hartanti, Monica Dwi (Future Science / FSH-PH Publications, 2023)
Post Traumatic Stress Disorder (PTSD) is common in COVID-19 survivors and can be caused by a variety of stressors, including the duration of infection, severity, and location of isolation when infected with COVID-19. Furthermore, public anxiety caused by the rapid increase in the number of cases and deaths caused by COVID-19 plays a role in the occurrence of PTSD. To reduce the risk of mental disorders, psychosocial support is required. The purpose of this study was to describe the incidence of PTSD in COVID-19 survivors, to describe aspects of psychosocial support for COVID-19 survivors, and to assess the relationship between stressor factors and psychosocial support and the occurrence of PTSD in COVID-19 survivors. This research used an analytical observational research design with a cross sectional approach, involving 149 respondents aged 17-65 years, 52 men and 97 women from the COVID-19 survivor community known as COVID Survivor Indonesia (CSI) in DKI Jakarta. The Medical Outcomes Study–Social Support Survey (MOS-SSS) and The Impact Of Event Scale-Revised (IES-R) questionnaires were distributed via Google Form to collect data. Data was processed and analyzed using the Statistical Package for Social Sciences (SPSS) for Windows version 26.0, and results were analyzed using descriptive univariate and bivariate using Chi Square. There is a significant relationship between stressor factors and the occurrence of PTSD, specifically the duration of infection with COVID-19 (P = 0,026), severity when infected with COVID-19 (P = 0,027), and place of isolation when infected with COVID-19 (P = 0,023). Furthermore, there was a significant relationship between psychosocial support and the occurrence of PTSD (p = 0,001). Management of COVID-19 patients is required to detect stressor factors and provide psychosocial support so that COVID-19 survivors can return physical and psychological health.